Measuring attitude towards learning science in Malaysian secondary school context: implications for teaching - Syed Hassan, Sharifah Sariah (Taylor & Francis, 2018)
The aim of education is to ensure a holistic development towards knowledge and well-being. Despite exhaustive effort on embedding twenty-first century skills in science teaching, students show lack of interest to learn and pursue their science careers. This present study has attempted to develop an instrument for measuring attitude towards science learning. The purpose was to ensure valid items were identified to measure all aspects of attitude namely affect, behaviour and cognitive. The study of attitude in science will determine the direction on how teaching strategies can be successful in promoting interest in learning. The study has been underpinned from the theories related to Theory of Reasoned Action, Constructivist learning and Connectivism. Samples from three secondary schools were selected based on proportionate stratified random sampling. 350 samples were targeted to respond to self-constructed questionnaires. Confirmatory Factor Analysis (CFA) was employed to prove the hypothesised 5-factor measurement model. The results have supported a model fit with positive interactions between the factors are evident. The study has proven the theoretical contributions which embark on holistic development of an individual to ensure attitude is moulded. The emotional and spiritual aspects of learning are needed to ensure positive contribution to the social dynamic. In this paper, the discussions are elaborated from the standpoints of theories and practical importance. The results have contributed to a theoretical model of science teaching method.